Satellite data communications (TCP/IP over satellite): performance issues / Haslina Tamsir - Tamsir, Haslina (1998)
This paper focuses on understanding the principles of Satellite Data Communication, study the concepts and the implementation of Transmission Control Protocol/Internet Protocol (TCP/IP) Protocol Suite over satellite links. The performance over satellite links especially the throughput is investtgated by simulation using the commercial communication software design tooi. The main objective of the study is to evaluate the throughput performance of TCP/IP over satellite links. The throughput of TCP/IP over satellite have been investigated in four conditions; 1. Without congestion control and in error firee condition. 2. Without congestion control and in error condition. 3. With congestion control and in error free condition. 4. With congestion control and in error condition. From the investigation, the first condition proved that in error free and without employing the congestion control algorithms, 5 data connections can fully utilize the available bandwidth. However, when congestion control algortthm was employed, only 2 data connections are needed to improve to the same bandwidth utilization. The present of errors for both situations with and without congestion control algorithms reduce the number of multiple data connection used.